Reki Terapi untuk Nyeri, Kecemasan, Stress dan Kualitas Hidup Pasien Paliatif Care - Fuadah, Samrotul; Waluyo, Agung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Research on complementary Reiki therapy in patients with chronic diseases needs to be critically reviewed to test the validity, results and relevance of scientific evidence (research results) so that new knowledge can be applied in professional practice. The method used was a systematic mapping study (scoping study) which was carried out in September-November 2021 in four databases, namely Elsevier, Pubmed, Science Direct, and ProQuest using keywords according to the MesH Term. The results of this research showed that there were 4 articles that had been evaluated using the PRISMA checklist and these 4 articles stated that Reiki therapy could control, reduce pain, anxiety and stress in patients with palliative care. In conclusion, Reiki therapy is an effective therapy in reducing the symptoms and pain faced by patients with palliative care, such as pain, anxiety, stress and quality of life. Keywords: Palliative Care, Reiki, Complementary Therapy